2016
DOI: 10.3389/fpls.2016.01402
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Triacylglycerol Mobilization during Seed Germination and Early Seedling Growth in Arabidopsis Containing Nutritionally Important Polyunsaturated Fatty Acids

Abstract: There are now several examples of plant species engineered to synthesize and accumulate nutritionally important polyunsaturated fatty acids in their seed triacylglycerols (TAG). The utilization of TAG in germinating seeds of such transgenic plants was unknown. In this study, we examined the TAG utilization efficiency during seed germination in transgenic Arabidopsis seeds containing several examples of these fatty acids. Seed TAG species with native fatty acids had higher utilization rate than the TAG species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 27 publications
(35 reference statements)
1
14
0
Order By: Relevance
“…However, the mechanisms that biochemically inhibit plastid localized acetyl‐CoA carboxylase activity due to the production of HFA in the endoplasmic reticulum are still unknown. Similar reduced oil content within transgenic seeds accumulating novel fatty acids has also been reported for a range of different transgenic plants and novel fatty acids produced (Knutzon et al., ; Larson, Edgell, Byrne, Dehesh, & Graham, ; Li et al., ; Mansour et al., ; Shrestha, Callahan, Singh, Petrie, & Zhou, ). Therefore, successful TAG composition engineering will also need to successfully recover any reduced oil penalty that novel fatty acid production has on seed oil accumulation.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…However, the mechanisms that biochemically inhibit plastid localized acetyl‐CoA carboxylase activity due to the production of HFA in the endoplasmic reticulum are still unknown. Similar reduced oil content within transgenic seeds accumulating novel fatty acids has also been reported for a range of different transgenic plants and novel fatty acids produced (Knutzon et al., ; Larson, Edgell, Byrne, Dehesh, & Graham, ; Li et al., ; Mansour et al., ; Shrestha, Callahan, Singh, Petrie, & Zhou, ). Therefore, successful TAG composition engineering will also need to successfully recover any reduced oil penalty that novel fatty acid production has on seed oil accumulation.…”
Section: Introductionsupporting
confidence: 65%
“…The likely reason for the low oil content of the transgenics relative to the nontransgenic control was that similar to wild type (Li et al, 2006) the fae1 line has the ability to greatly increase fatty acid synthesis in response to additional light, but in each transgenic line the novel fatty acid-induced inhibition of fatty acids (Bates et al, 2014) limits this response to varying degrees (Figures 1b and 4b). Considering that reduced seed oil content has been indicated in many different instances of novel fatty acid (Knutzon et al, 1999;Larson et al, 2002;Li et al, 2012;Lunn et al, 2018;Mansour et al, 2014;Shrestha et al, 2016), it is likely that other novel fatty acid engineering strategies will demonstrate similar seed oil results based on light conditions. When interpreting conclusions on the effect of novel fatty acid engineering on total seed oil accumulation, we found that both the 5) is likely due to the differences in rate of fatty acid synthesis versus fatty acid modification.…”
Section: Effect Of Photoperiod Length On Novel Fatty Acid Engineerimentioning
confidence: 99%
“…Total lipids extracted from 1 mg of T 4 homozygous seeds were dissolved 1 mL of butanol/methanol (1/1, v/v) containing 10 mM butylated hydroxytoluene. DAG and TAG species that contained DHA were analyzed using MRM mode by LC-MS as previously described ( Shrestha et al, 2016 ). The ratio of the peak area of individual species among total DHA-containing DAGs or TAGs was calculated.…”
Section: Methodsmentioning
confidence: 99%
“…The relationship between seed reserves and germination has been studied mainly in economically-important species such as Oryza sativa ( Sun et al, 2015 ), Glycine max ( Bellaloui et al, 2017 ), Sorghum bicolor ( Elmaki et al, 1999 ), Linum usitatissimum ( Kanmaz and Ova, 2015 ) and in the model plant species Medicago truncatula ( Vandecasteele et al, 2011 ) and Arabidopsis thaliana ( Shrestha et al, 2016 ). These previous studies on seed reserve mobilization during germination have given little attention to wild grassland species and have mainly focused either on only one type of reserves ( Kim et al, 2009 ; Shaik et al, 2014 ) or a single species (usually crops) ( Goyoaga et al, 2011 ; Ataíde et al, 2013 ; Lopes et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%